Feasibility Analysis of Grade IX Arabic Textbook Based on Tomlinson's Theory - Fasya Fatharani Mumtaz; Asep Sopian; Nalahuddin Saleh (Jurnal Studi Guru dan Pembelajaran, 2024)
Textbooks play an essential role in learning, especially in foreign language learning such as Arabic, which has its complexities. The quality of textbooks greatly determines the success of the teaching and learning process. A good textbook must meet certain criteria to ensure its effectiveness in helping students understand the materials. However, there are currently many choices of Arabic textbooks. However, content errors are still found, so a feasibility analysis is required. This study evaluates the feasibility of an Arabic textbook for grade IX published by the Directorate of KSKK Madrasah, using Tomlinson's theory, which includes 16 criteria for good textbooks. This research uses qualitative methods with content analysis techniques. The first step in this research is to compile an instrument in the form of a checklist table consisting of several assessment indicators according to Tomlinson's criteria. Then, the textbook was analyzed comprehensively to assess the suitability of the content with the instrument. The obtained data were then calculated and converted into percentages to determine the feasibility category. The analysis results show that the Arabic textbook for grade IX is highly suitable for Tomlinson's criteria. With a score of 58 out of a maximum score of 64, or 90%, this textbook falls into the “Good” category. This conclusion is supported by high scores on most of the assessment indicators, indicating that this textbook meets the established standards in various aspects of foreign language learning. The Arabic textbook for grade IX is reckoned as a highly feasible learning media. However, some aspects still require improvement, such as aspects of variety, unplanned discourse, optional extras, etc. Improvements in these aspects aim to improve the quality of textbooks, which impacts the effectiveness of learning and ensures student achievement is in line with the expected competencies.